Warisan Visual dalam Komposisi Fasad Bangunan Kolonial sebagai Identitas Arsitektural di Jalan Jembatan Merah Surabaya - Soegiarto, Rayden Lauwirya; Dharmatanna, Stephanus Wirawan (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2025)
Colonial buildings in Surabaya are an important part of the city's architectural heritage, representing its visual identity and the result of acculturation between European and Indonesian cultures. This study aims to examine the composition of facades as elements that shape the visual character of colonial buildings in the Jembatan Merah area. The study uses a qualitative-descriptive approach with a case study method, involving field observations, visual documentation, and analysis based on D.K. Ching's theory of visual composition and Hamid Shirvani's theory of visual character of the environment. Four colonial buildings were selected as objects of study: Singa Building, PTPN X Building, Maybank Building, and NILLMIJ Building. The results of the study show that the four buildings share common principles in terms of geometry, symmetry, scale, and façade rhythm, which create visual cohesion in the urban landscape. The proportion of openings ranging from 25–40% reflects the design adaptation to the tropical climate through the optimisation of natural ventilation, while the dominant proportion of massive surfaces reinforces the monumental impression characteristic of colonial architecture. Façade elements such as prominent main doors, limasan roofs, and decorative ornaments play an important role in shaping the visual identity of the buildings. These findings confirm that façade composition is an integral part of the visual heritage that must be preserved in efforts to conserve and revitalise historic areas. Understanding this visual composition structure is expected to serve as a reference in contextual design planning that is sensitive to the city's historical values.